2010
DOI: 10.1159/000284396
|View full text |Cite
|
Sign up to set email alerts
|

Is Sex Hormone Priming in Peripubertal Children prior to Growth Hormone Stimulation Tests Still Appropriate?

Abstract: Low growth hormone (GH) secretion during puberty may stem from either a permanent GH axis abnormality or from transient GH deficiency secondary to lack of sex hormones. Although well known to enhance stimulated GH secretion in pre- or early puberty, sex hormone priming for the evaluation of the function of the GH-IGF-I axis remains controversial. Many pediatric endocrinologists consider that omission of such priming during the preadolescent period decreases the specificity of GH stimulation tests and increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…Recently, Lazar and Phillip [25] have reviewed the available published data and suggested that priming should be considered only in adolescents with pubertal delay, girls aged 11.5-12 years and boys aged 13-13.5 years, exhibiting no evidence of puberty or only initial signs. The children evaluated in our study showed a mean chronological age of 11.34 ± 2.99 years (boys) and 9.87 ± 2.14 years (girls).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lazar and Phillip [25] have reviewed the available published data and suggested that priming should be considered only in adolescents with pubertal delay, girls aged 11.5-12 years and boys aged 13-13.5 years, exhibiting no evidence of puberty or only initial signs. The children evaluated in our study showed a mean chronological age of 11.34 ± 2.99 years (boys) and 9.87 ± 2.14 years (girls).…”
Section: Discussionmentioning
confidence: 99%
“…A sex hormone priming before GH stimulation tests was not performed in our cohort of children due to the absence of a consensus about this point and controversial data from the literature [24,25,26,27]. However, to reinforce the diagnosis of GHD, as auxological data we considered height (standard deviation, SD), height velocity (HV) 1 year before the diagnosis (SD) and height in comparison to the midparental height (SD).…”
Section: Methodsmentioning
confidence: 99%
“…However, not all paediatric endocrinologists agree that sex-hormone priming is required [45], since it only briely augments the GH response which then returns to suboptimal concentrations and this may lead to underdiagnosis of peri-pubertal children that could have beneited from GH treatment. Some authors recommend that priming may be considered only in adolescents with pubertal delay (girls aged >11.5 12 years and boys aged >13 13.5 years) with no signs of puberty or only initial ones [46]. Therefore, at present there is no agreement on the use of priming.…”
Section: Provocative Gh Testingmentioning
confidence: 99%
“…According to Lazar and Phillip from Israel, priming should not be routinely performed in every peripubertal child undergoing GH evaluation but considered only in adolescents with pubertal delay, i.e. girls >11.5-12 years and boys >13-13.5 years [4]. The guidelines of the Paediatric Endocrine Society suggested giving β-estradiol orally to both boys and girls on two evenings preceding the test.…”
Section: Introductionmentioning
confidence: 99%